2018
DOI: 10.1089/hum.2017.144
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac-Specific Expression of ΔH2-R15 Mini-Dystrophin Normalized All Electrocardiogram Abnormalities and the End-Diastolic Volume in a 23-Month-Old Mouse Model of Duchenne Dilated Cardiomyopathy

Abstract: Heart disease is a major health threat for Duchenne/Becker muscular dystrophy patients and carriers. Expression of a 6-8 kb mini-dystrophin gene in the heart holds promise to change the disease course dramatically. However, the mini-dystrophin gene cannot be easily studied with adeno-associated virus (AAV) gene delivery because the size of the minigene exceeds AAV packaging capacity. Cardiac protection of the ΔH2-R19 minigene was previously studied using the cardiac-specific transgenic approach. Although this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…In support of this, it was recently discovered that cardiac dystrophin interacts with a distinctive set of cellular proteins 155 . We also found that modification of the rod domain configuration substantially improved myocardial protection 156, 157. Heart rescue has only been studied in a few microgenes in mdx mice, and most of these studies have used the ΔR4–23/ΔC microgene 55, 59, 63, 65, 158, 159, 160.…”
Section: Main Textmentioning
confidence: 71%
“…In support of this, it was recently discovered that cardiac dystrophin interacts with a distinctive set of cellular proteins 155 . We also found that modification of the rod domain configuration substantially improved myocardial protection 156, 157. Heart rescue has only been studied in a few microgenes in mdx mice, and most of these studies have used the ΔR4–23/ΔC microgene 55, 59, 63, 65, 158, 159, 160.…”
Section: Main Textmentioning
confidence: 71%
“… 23 In a more recent study, a mini-dystrophin construct optimized for the heart more effectively rescued cardiac function in aged BL10/ mdx mice. 48 These studies highlight the importance of tissue-specific mini-gene construct design. It is also important to note that a fully optimized mini-gene will only produce a mild BMD phenotype in DMD patients.…”
Section: Discussionmentioning
confidence: 99%
“…Western blot. Proteins from heart and skeletal muscle were extracted according to our published protocol (31). Dystrophin was detected with a rabbit polyclonal antibody against the C-terminal domain (catalog RB 9024, 1:500, Thermo Fisher Scientific).…”
Section: Methodsmentioning
confidence: 99%